Translation Quality: a Housian Analysis - Rodrigues, Sara (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThe author comments on the translation quality assessment model developed by Juliane House and published in 1981. Although it is somewhat dated, this model has given the best results so far, and is a definite improvement over its predecessors.